Interpretasi Genetik Pola Pita Isozim pada Cherax quadricarinatus Hasil Budidaya di Purwokerto dan Bogor - Dian Bhagawati; Muh. Nadjmi Abulias (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
A study on genetic interpretation of isozyme band patterns of C. quadricarinatus cultured in Purwokerto and Bogor showed the good visualization of aspartat transaminase, alkohol dehidrogenase, malat dehidrogenase, esterase and acid phosphatase. Twelve loci resulted low level of polymorphism (P= 0,25) and also low valve of heterozygosity (H= 0,09). It indicated that the genetic diversity of both populations was low.